The role of audio-visual media in consolidating the position of the Arabic language in the Arab cultural imagination - Dr. Muhammad Abdel Hamid Dhaidan (Peerian Journals Publishing, 2024)
There is no doubt that the language enjoys a great place as one of the most important means of communication and transfer of ideas and experiences between people. The Arabic language has a great peculiarity because it is linked by strong ties with those who use it, namely the Arab peoples, because it represents history, customs, traditions, and civilization, and above all, its connection to the Islamic religion and the language of the Holy Qur’an. It is It was not only a tool for expression, but rather an Arab and Islamic intellectual, cultural and social treasure. It is also the identity of Muslim peoples with which they move towards others
Keywords: Muslim; identity; treasure; Arab